Callistosporium pinicola (Basidiomycota), a fungus species new to Poland - Marek Halama; Ryszard Rutkowski (Acta Mycologica, 2014)
Basidiomata of Callistosporium pinicola were collected in years 2012–2013, on strongly decayed fallen trunks of Picea abies and Abies alba on two remote sites, localized in North-eastern and southern Poland. These localities represent the first records of this fungus in Poland. A full description and illustration of C. pinicola based on Polish specimens are provided and the distinguishing features and delimitation of the species are briefly discussed. The ecology of C. pinicola, its general distribution and threat are also presented. As all specimens of C. pinicola were collected only in recent years we suggest that this species is increasing its distribution in Poland. However, we cannot rule out the possibility that, because of its cryptic nature, C. pinicola has been much overlooked in the past.